THE EFFECTIVENESS OF COLD COMPRESSES AND STORY DISTRACTION TECHNIQUES TOWARDS INFUSED INSERTION PAIN - Wilia Wahyuni; Handono Fatkhur Rahman; Heri Siswanto (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2020)
Installation of infusion is an action that is quite often done in the hospitalespecially at emergency room. The proceeding of infusion can cause pain that is felt by the client, so it requires non pharmacological therapy among them are cold compress therapy and storytelling distraction technique. The purpose of the research is to find out the effectiveness of cold compress and distractions storytelling about infusion insertion pain. The reseach design used is pre-experimental design with post test only design approach, sampling using purposive sampling technique with sample size of 25 respondents in the cold compress group and 25 respondents at distraction storytelling group. The instrument for collecting data uses an observation sheet. The results of this research indicate the average pain in the group of respondents who received cold compress treatment during infusion 1,20, whereas in the group that gets distraction tells the average value is 2,56. The statistical test results are used Mann Whitney’s test obtained value P (0,000) < ά (0,05) that is, there are significant differenees between cold compress pain storytelling to infusion insertion pain. Therefore it can be concluded that cold compress are more effective at reducing infusion insertion pain than storytelling distraction technique.